Novel PIM1 substrates and senescence-specific proteomic changes in human lung cancer cells - Tuomaala, Joel (My University, 2019)
PIM1 belongs to the PIM family of constitutively active serine threonine kinases. PIM1 regulates cell growth, proliferation and survival and is upregulated in several types of cancer, such as triple negative breast cancer, prostate cancer and colon cancer, making it a promising target for cancer research. PIM1 may also be involved in the regulation of cellular senescence, as most regulatory pathways PIM1 participates in are altered in senescence. Regulation of senescence may in turn be relevant from the cancer standpoint, as senescence is a major inhibitor of cancerous growth. PIM1 has substrates that regulate senescence induction as well as up-regulators that are activated under senescence-inducing conditions. In this study, I used the Kinase-Interacting Substrate Screening (KISS) method to identify novel PIM1 substrates from both senescent and normal lung cancer cell populations. In addition, other proteins in the samples were compared between the senescent and normal cells, and novel candidate proteins for senescence-related proteomic changes were identified. The KISS assay is based on allowing substrates to bind to the bait kinase followed by mass spectrometry-based identification of the bound substrates. The KISS assay has the theoretical potential to capture all possible substrates in a given sample in one go, since a small amount of each substrate is expected to be bound and phosphorylated. In practice, however, substrate detection is limited by the transiency of substrate binding and therefore by the sensitivity and specificity of mass spectrometry. The KISS assay can be used for screening new substrate candidates, but detection of a given known substrate is not likely. In the end one previously described substrate and 12 novel PIM1 substrate candidates were identified, along with variations in their expression levels between normal and senescent samples.

PIM1 on konstitutiivisesti aktiivinen seriini-threoniini-kinaasi, joka kuuluu PIM-kinaasiperheeseen. PIM1 säätelee solujen kasvua, jakautumista ja selviytymistä. Sen ekspressio on kohonnut esimerkiksi kolmoisnegatiivisessa rintasyövässä, eturauhassyövässä ja paksusuolensyövässä, mikä tekee siitä lupaavan kohteen syöpätutkimukselle. PIM1 saattaa osallistua seneskenssin säätelyyn, sillä monet signalointireitit joihin se osallistuu muuttuvat seneskenssissä. Seneskenssin säätely voi olla merkittävää syövän näkökulmasta, sillä seneskenssi on voimakas syöpäkasvun inhibiittori. PIM1-kinaasilla on sekä substraatteja, jotka säätelevät seneskenssin indusointia, että säätelytekijöitä, jotka aktivoituvat vasta seneskenssiä indusoivissa olosuhteissa. Tässä tutkimuksessa käytin kinaasi-susbstraatti-interaktioon perustuvaa substraattien seulontamenetelmää (KISS-menetelmä) tunnistaakseni uusia substraatteja PIM1-kinaasille. Etsin substraatteja normaaleista ja seneskenteistä keuhkosyöpäsoluviljelmistä. PIM1-kinaasin substraattien lisäksi vertailin muiden proteiinien määriä viljelmien välillä. KISS-menetelmä perustuu substraattien sitoutumiseen tutkittavan kinaasin pintaan, minkä jälkeen sitoutuneet substraatit tunnistetaan massaspektrometrialla. KISS-menetelmällä voidaan teoriassa tunnistaa näytteestä kaikki mahdolliset substraatit kerralla, sillä pieni määrä jokaista substraattia todennäköisesti tarttuu aina tutkittavaan kinaasiin. Käytännössä tunnistusta rajoittaa sitoutumisen määrä ja voimakkuus, ja siten massaspektrometrian tarkkuus ja spesifisyys. KISS-menetelmä toimii hyvin uusien substraattien etsimisessä, mutta minkään tietyn ennalta tunnetunkaan substraatin havaitseminen ei ole taattua. Tutkimuksen lopputuloksena PIM1-kinaasille tunnistettiin 12 täysin uutta substraattikandidaattia ja yksi ennalta tunnettu substraatti. Substraattien lisäksi löydettiin uusia seneskenssiin liittyviä muutoksia proteiiniekspressiossa.
Keywords: PIM1, substrate screening, KISS, mass spectrometry, senescence